2017
DOI: 10.7863/ultra.16.06079
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Elastography of the Neonatal Brain: Preliminary Study

Abstract: Neonatal intracranial regions showed different elasticity, which could be accessed by strain elastography. These normal findings should prompt future studies investigating the use of ultrasound elastography in the neonatal brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…13,15,16 SWE maintained the same thermal effect as pulsed Doppler ultrasound already authorized in obstetrics 18 and previously directed SWE with neonatal tissue studied by Kim et al did not report any adverse outcome. 19 Several previous studies have widely employed SWE in singleton pregnancy. Carlson et al reported that treatment of nonpregnant cervix with prostaglandins, and the induction of labor with prostaglandins which showed to diminish the shear wave speed in the cervix.…”
Section: Introductionmentioning
confidence: 99%
“…13,15,16 SWE maintained the same thermal effect as pulsed Doppler ultrasound already authorized in obstetrics 18 and previously directed SWE with neonatal tissue studied by Kim et al did not report any adverse outcome. 19 Several previous studies have widely employed SWE in singleton pregnancy. Carlson et al reported that treatment of nonpregnant cervix with prostaglandins, and the induction of labor with prostaglandins which showed to diminish the shear wave speed in the cervix.…”
Section: Introductionmentioning
confidence: 99%
“…Their measurements of the elasticity of neonatal cerebral white and grey matters in a group of preterm and term infants with ARFI showed that stiffness across all regions was lower in preterm infants than in those born in term (22). The same conclusion that the degree of elasticity of a certain region changed according to the gestational age brought results obtained by using the SE by Kim et al (2017) (23). Concordantly, Albayrak and Kasap (2018) presented results gained by using 2D-SWE in term as well as preterm neonates, where the stiffness values of thalamus and periventricular white matter were higher in term newborns.…”
Section: Clinical Application In Neonatologymentioning
confidence: 85%
“…Recently, several scholars have applied US elastography to neonatal brains, showing that full-term newborn brains show greater hardness than those of preterm neonates. Kim et al 9 performed strain elasticity imaging on 21 healthy neonates. Compared with the white matter around the ventricle, the caudate nucleus, and the subcortical white matter, the cerebral cortex gray matter showed higher elasticity, and the caudate nucleus was less elastic than the white matter around the lateral ventricle.…”
Section: Normal Performance Of Cranial Us Elastographymentioning
confidence: 99%
“…An increasing number of studies using US elastography to investigate cranial diseases have been conducted in recent years. [6][7][8][9]…”
mentioning
confidence: 99%